Trapping in proton irradiated p+-n-n+ silicon sensors at fluences anticipated at the HL-LHC outer tracker. (22nd April 2016) - Adam, W.; Bergauer, T.; Dragicevic, M.; Friedl, M.; Fruehwirth, R.; Hoch, M.; Hrubec, J.; Krammer, M.; Treberspurg, W.; Waltenberger, W.; Alderweireldt, S.; Beaumont, W.; et al.
Abstract: The degradation of signal in silicon sensors is studied under conditions expected at the CERN High-Luminosity LHC. 200 μ m thick n-type silicon sensors are irradiated with protons of different energies to fluences of up to 3 · 10 15 neq/cm 2 . Pulsed red laser light with a wavelength of 672 nm is used to generate electron-hole pairs in the sensors. The induced signals are used to determine the charge collection efficiencies separately for electrons and holes drifting through the sensor. The effective trapping rates are extracted by comparing the results to simulation. The electric field is simulated using Synopsys device simulation assuming two effective defects. The generation and drift of charge carriers are simulated in an independent simulation based on PixelAV. The effective trapping rates are determined from the measured charge collection efficiencies and the simulated and measured time-resolved current pulses are compared. The effective trapping rates determined for both electrons and holes are about 50% smaller than those obtained using standard extrapolations of studies at low fluences and suggest an improved tracker performance over initial expectations.